EFEKTIFITAS PENGGUNAAN DANA BANTUAN OPERASIONAL SEKOLAH PADA SEKOLAH DASAR 014 TANJUNG REDEB KABUPATEN BERAU: EFEKTIFITAS PENGGUNAAN DANA BANTUAN OPERASIONAL SEKOLAH PADA SEKOLAH DASAR 014 TANJUNG REDEB KABUPATEN BERAU - Arkam (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The purpose of this study is to find out and analyze the purpose of the research conducted is to determine the effectiveness of the use of school operational assistance funds in State Elementary Schools 014 Tanjung Redeb, Berau Regency. The sample used in this study is data on the Activity Plan and Budget of elementary school 014 Tanjung Redeb, Berau Regency in 2015 – 2022 using quantitative descriptive analysis techniques with an approach using the Effectiveness Ratio indicator. Based on the results of the study, it can be seen that the average level of effectiveness of the use of school operational assistance funds in State Elementary Schools 014 Tanjung Redeb, Berau Regency in 2015-2022 is at an effectiveness ratio of 93.5%, which is on the